Critical analysis of communicative intentionality and understanding of discourse in social sciences - Rosas Domínguez, Javier Dionisio (2019)
Objective. To determine the relationship that exists between the critical analysis of communicative intentionality and understanding of discourse in social sciences, in students of the School of Economic Sciences of UNAS, Leoncio Prado, 2017. Methods. Research was carried out within the framework of a quantitative approach. Design used was a non-experimental cross-sectional one. Population comprised of 54 students, while the sample was 40 students. Results. A 95 % confidence interval with a 5 % margin of error. Therefore, p <0.05 and Pearson’s coefficient were found at 0.944. Consequently, there is a relationship between the analysis of communicative intent and the understanding of discourse. While the results in relation to the specific hypothesis is: In the first hypothesis, p <0.05 and Pearson’s coefficient at 0.604. In the second hypothesis, p <0.05 and the correlation coefficient at 0.697. Finally, in the third hypothesis, p <0.05 and Pearson’s correlation coefficient at 0.466. Conclusion. There is a positive and significant correlation between critical analysis of communicative intent and understanding of discourse in students of the School of Economic Sciences of Universidad Agraria de la Selva. Likewise, there is a positive and significant correlation between critical analysis of communicative intentionality and dimensions of speech understanding. Therefore, the more critical analysis of communicative intentionality, the greater the understanding of discourse in social sciences.